Application of VIP Care in Patients with Advanced Tumors in the Western Region of China. (31st August 2022) - Zheng, Xiaoqin; Peng, Yanqiong; Liu, Chonghua; Li, Fei; Zhang, Haiying; Liao, Jia; Wu, Guirong; Zeng, Xiaomei; Xie, Nan
Abstract : Objective . The objective of this study is to explore the application of a very important person (VIP) intervention mode in patients with advanced tumors in the western region of China. Methods . One hundred and sixty-three patients were randomly divided into a control and experimental groups. The control group received routine care, and the experimental group received VIP future care. The willingness to end-of-life treatment, decision-making certainty, and quality of life were compared between the two groups before intervention (T0), after intervention (T1), and 1 month after intervention (T2). Results. There were no significant differences in the basic data of the two groups. Unlike the control group, the experimental group preferred palliative care at the end of T1 (P < 0.05 ), and the acceptance rate of cardiopulmonary resuscitation and mechanical treatment decreased significantly. After the VIP intervention, the patient was transferred to the intensive care unit (ICU) (P < 0.05 ). After 1 month of intervention (T2), the results showed that the overall quality of life, physical discomfort, negative emotions, care and support, survival predicament, and lifetime value of the patients were significantly higher than those before the intervention (all P < 0.05 ). Decision certainty results showed that the differences between the T0, T1, and T2 time points and the interaction between groups and time were statistically significant, and the interaction was more significant at T2 (P < 0.05 ). Conclusion . VIP future care can change patients' wishes for end-of-life care, improve patients' and quality of life, and increase patient decision-making certainty.